2019
DOI: 10.4238/gmr18331
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Digital image analysis to quantify genetic divergence in passion fruit (<i>Passiflora</i> <i>edulis</i>) seeds

Abstract: Passion fruit is a native fruit of tropical America, with Brazil being the world's leading producer and consumer of this fruit, with an estimated annual production of 554,598 Mg, and yield of 13,500 kg.ha-1 Phenotyping through digital images has been used to evaluate morphological characteristics of seeds. Knowledge of the degree of genetic divergence plays an important role, as it assists in the adoption of appropriate strategies for improvement in passion fruit populations.. The objective of this work was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
5
1
1
Order By: Relevance
“…Contrary to this study, Fachi et al (2019) and Krause et al (2017) found a greater contribution to the analysis of genetic divergence, using the Ward-MLM method, in seed geometry traits. However, in the present study, the geometry variables were also predominant for the discrimination of the genotypes under study.…”
Section: Genetic Dissimilarity In S 2 Families Of P Guajavacontrasting
confidence: 99%
“…Contrary to this study, Fachi et al (2019) and Krause et al (2017) found a greater contribution to the analysis of genetic divergence, using the Ward-MLM method, in seed geometry traits. However, in the present study, the geometry variables were also predominant for the discrimination of the genotypes under study.…”
Section: Genetic Dissimilarity In S 2 Families Of P Guajavacontrasting
confidence: 99%
“…The results obtained in this study and those described by Torres et al (2019), Fachi et al (2019, and Krause et al (2017) clearly demonstrate that the contribution of each variable to determine genetic divergence can vary according to species, genotype, and family.…”
Section: Digital Phenotyping Meanssupporting
confidence: 77%
“…The C1, C2 and C3 variables did not contribute in any of the adopted strategies. Fachi et al (2019) used digital phenotyping in seeds of 98 full-sib families of passion fruit and observed that the geometry descriptors were those that most contributed to genetic divergence between families. The C1, C2 and C3 variables also did not contribute to the calculation of genetic diversity in seeds of Passiflora edulis.…”
Section: Digital Phenotyping Meansmentioning
confidence: 99%
“…Los marcadores morfológicos, que son características que se pueden distinguir a nivel visual, pueden ser utilizados como herramienta para la caracterización (Sattar Khan et al, 2015). En Passiflora las características morfológicas de las semillas han demostrado ser útiles para la clasificación taxonómica de sus especies (Fachi et al, 2019;Mezzonato-Pires et al, 2017;Torres et al, 2019).…”
Section: Discussionunclassified